Facial Fabrication and Characterization of Novel Ag/AgCl Chloride Ion Sensor Based on Gel-Type Electrolyte - Kim, Seil; Park, Gwangryeol; Ahn, Hong-Ju; Yoo, Bung Uk; Song, In-Hyuck; Lee, Kyu-Hwan; Kim, Kwang Ho; Lim, Jae-Hong; Lee, Joo-Yul (Frontiers in Chemistry, 2020)
A novel silver–silver chloride (Ag/AgCl) chloride ion (Cl–) sensor based on the electrochemical principles and comprising a gel-type internal electrolyte and diatomite ceramic membrane was fabricated. The Cl– sensing characterization included determining the response potential, response time (T90), recovery time (D10), and reliability of the sensor, which were systemically investigated at different Cl– concentrations. The gel-type electrolyte was synthesized by mixing with hydroxyethyl cellulose as the main component. The diatomite ceramic membrane (DCM) with fine pore sizes played an important role in preventing electrolyte leakage from the ion selective electrode. The as-fabricated Ag/AgCl chloride ion sensor could detect Cl– in 10 mM to 500 mM KCl solutions with good linearity. The best response and recovery times of 0.5 s and 0.1 s, respectively, were obtained with 10 mM KCl. A wireless sensing system based on Arduino software was also investigated to measure the response potential of Cl– in an electrolyte. The sensor showed high reliability with a low standard error of measurement. This type of sensor is a key component in fabricating a wireless Cl– sensor for applications in reinforced concrete (RC) structures with favorable performances.